PENINGKATAN KUALITAS DIRI DALAM MEMBANGUN HUBUNGAN ANTAR ANGGOTA KELUARGA - Santoso, Joko (Sekolah Tinggi Teologi Kristus Alfa Omega, 2018)
Family is the smallest unit in human life consisting of father, mother and child. Family is built with the aim of achieving life expectancy in peace and happiness. So, to achieve this is done in such a way with various ways, efforts and efforts. Each takes their roles and responsibilities and according to ability. But in reality, in the process of achieving goals there are many obstacles and problems that cannot be avoided. Because in one other family are interrelated, influence each other, and clash with each other. So that it causes disruption of relationships between family members. Not even the few that ended in separation. This background occurs because of the personal nature of each person who does not have self quality that must be improved in building relationships within the family continuously from time to time.